A new design of catalytic tube reactor for hydrogen production from ethanol steam reforming. (1st December 2020) - Chen, Wei-Hsin; Lu, Chen-Yu; Tran, Khanh-Quang; Lin, Yu-Li; Naqvi, Salman Raza
Graphical abstract: Highlights: A novel catalytic tube reactor is designed for efficient H2 production with low cost. The influences of six operating parameters on ESR performance are studied. Kinetic mechanism becomes dominant at high reaction pressures. When catalyst thickness/tube diameter = 0.33, C2 H5 OH conversion achieves almost 100%. H2 yield is as high as 3.13 mol (mol C2 H5 OH) −1 when using 4 tubes. Abstract: A new design of the catalytic tube system with a crossflow configuration, featured by low catalyst usage and cost, is developed using computational fluid dynamics (CFD). Meanwhile, the kinetics of ethanol steam reforming over a nickel-based catalyst is conducted based on experimental measurements. The effects of six parameters on ethanol conversion and H2 yield are evaluated; they are the reaction pressure, the Reynolds number (Re), the ratio of catalyst thickness to tube diameter (T/D ratio), the ratio of tube diameter to channel width (D/W ratio), the steam-to-ethanol molar ratio (S/E ratio), and the number of tubes. The results indicate that the higher the reaction pressure, the better the ESR performance, as a result of the dominant kinetic mechanism on ESR in the special geometric structure of this study. Increasing the D/W or T/D ratio can effectively improve the ethanol conversion and H2 yield, stemming from the diminish of gas hourly space velocity (GHSV). It is observed that the ethanol conversion has no significant growth when the S/E ratio is over 4, revealing the co-effective choice of the S/E ratio below 4. Increasing the number of tubes raises the ethanol conversion and attains 97% conversion when using four tubes. However, the influence of the altered Reynolds number on the performance is insignificant. When the T/D ratio is lifted to 0.33, the ethanol conversion achieves almost 100%. Overall, the newly designed catalytic tube system with low catalyst usage is a promising reactor that can be applied in ESR for efficient hydrogen production.